Long-Term Clinical Outcomes of Intercalary Allograft Reconstruction for Lower-Extremity Bone Tumors. (17th June 2020) - Sanders, P.T.J.; Spierings, J.F.; Albergo, J.I.; Bus, M.P.A.; Fiocco, M.; Farfalli, G.L.; van de Sande, M.A.J.; Aponte-Tinao, L.A.; Dijkstra, P.D.S.
Abstract : Background: Improved survival rates for patients with primary bone tumors of the extremities have increased the demand for reliable and durable reconstruction techniques. Some authors have stated that, after successful ingrowth, allografts are a durable long-term solution. This hypothesis is largely based on small studies with short-to-midterm follow-up. In order to determine the durability of intercalary allograft reconstructions in the lower extremities, we evaluated the long-term clinical outcomes at a minimum of 10 years. Methods: All patients who received an intercalary allograft reconstruction in a lower extremity between 1980 and 2006 were included in this retrospective multicenter cohort study. One hundred and thirty-one patients with a median age of 19 years were included. Eighty-nine (68%) had a femoral reconstruction, and 42 (32%) had a tibial reconstruction. The most prevalent diagnoses were osteosarcoma (55%), Ewing sarcoma (17%), and chondrosarcoma (12%). The median follow-up was 14 years. A competing risk model was employed to estimate the cumulative incidences of mechanical failure and infection. Patient mortality or progression of the disease was used as a competing event. Results: Nonunion occurred in 21 reconstructions (16%), after a median of 16 months, and was associated with intramedullary nail-only fixation (p < 0.01) and fixation with nonbridging plate(s) (p = 0.03). Allograft fracture occurred in 25 reconstructions (19%) after a median of 42 months (range, 4 days to 21.9 years). Thirteen (52%) of the allograft fractures occurred within 5 years; 8 (32%), between 5 and 10 years; and 4 (16%), at >10 years. With failure for mechanical reasons as the end point, the cumulative incidences of reconstruction failure at 5, 10, and 15 years were 9%, 14%, and 21%, respectively. Conclusions: Intercalary allograft reconstruction is an acceptable reconstructive option, mainly because of the absence of superior alternatives with a known track record. However, a considerable and continuing risk of mechanical complications should be taken into account. Level of Evidence: Therapeutic Level IV . See Instructions for Authors for a complete description of levels of evidence.